Can NNP be used for welfare comparisons? - Geir B. Asheim (University of Oslo, Department of Economics, 2005)
This paper contains a critical assessment of the claim that nnp can be used for welfare comparisons. The analysis assumes that national accounts are comprehensive (in particular, “greened” by taking into account environmental amenities and natural resource depletion), but does not assume optimal resource allocation. The general conclusion is that greater nnp does not correspond to welfare enhancement, unless the net investment flows are revalued. Real utility-nnp, and real measurable nnp made comparable across time by means of a consumer price index, allow for such revaluation, and thus indicate welfare improvement.
Keywords: C43; D60; O47; Q01; 330; National income accounting; dynamic welfare; Volkseinkommen; Volkswirtschaftliche Gesamtrechnung; Wohlfahrtstheorie